Myeloid Sarcoma of Orbits: Effectiveness of a Low-Dose Radiation Regimen. (9th September 2018) - Ravisankar, Shyam; Levy, Yair; Shah, Maya
Abstract : Acute myeloid leukemia (AML) can present with extramedullary involvement known as myeloid sarcoma (MS). We present the case of a young woman who was diagnosed with AML and MS in bilateral orbits, brain, omentum, and retroperitoneum. She was treated with induction chemotherapy. Low-dose radiation was given to the orbits due to visual symptoms which resulted in complete response. The use of radiation therapy in orbital MS has not been studied extensively, and low dose may be adequate to achieve complete remission (CR) in selected patients.